PRÁCTICAS CULTURALES, CONSERVACIÓN Y TURISMO: EL CASO DEL MÚRICE (PLICOPURPURA PATULA PANSA) EN COSTA RICA - Juárez Nogueira, María del Rocío (Universidad de Costa Rica, 2021)
This article provides a general reflection about the implications of conservation policies and tourism in the practice of dyeing with murice by the brunka people. Through the documentary review, interviews with specialists on the subject, as well as the ethnographic work carried out in the Boruca area during the months of January and February 2015, the enclosure processes of a common disposal natural resource —like the murix— are analyzed; as well as the strategies of the brunka dyers to continue with said activity.